СКОРОСТИ ПРОДОЛЬНЫХ ВОЛН В ВЕРХНЕЙ ЧАСТИ ЗЕМНОЙ КОРЫ ТИХОГО ОКЕАНА К ВОСТОКУ ОТ КАМЧАТКИ - Карп Борис Яковлевич; Медведев Сергей Николаевич (My University, 1989)
Seismic studies conducted using 18 profiles with seismoacoustic radio buoys and airguns on the shelf and continental slope of East Kamchatka and at the Obruchev Rise made it possible to determine velocities in the sedimentary layer and acoustic basement. Velocity in the coastal shelf increases with depth together with the gradient of 1.8—2.0 s-1 and in the off-shelf with the gradient of 1.4—1.5 s-1. Velocities near the bottom of the coastal shelf are 2,25— 3.5 km/s. Velocity variations in the continental slope sediments can be described by equation v= 1.75+0.51 Z. Variations at the Obruchev Rise and in the regions adjacent to the deep sea basin can be described by equation v= 1.55+0.74 Z. Z is the depth beneath the bottom in km. The gradient is measured in (s-1), velocity in (km/s).
Keywords: ДОННЫЕ ОСАДКИ; АКУСТИЧЕСКИЙ ФУНДАМЕНТ; ОПРЕДЕЛЕНИЕ СКОРОСТЕЙ ПРОДОЛЬНЫХ СЕЙСМИЧЕСКИХ ВОЛН; ГОДОГРАФЫ ВОЛН; 550.834